Simulation of switching effects in electrically dipolar manganites - Morchshakov, V.; Annaorazov, M. P.; Aybar, H. S.; Yang, C. P.; Troyanchuk, I. O.; Baerner, K. (Amer Inst Physics, 2009)
Electrical field induced transitions between metallic and insulating magnetic states have been reported in various manganites and, in particular, in oxygen deficient Nd0.7Sr0.3MnO3-delta with 0 >delta>0.2. In this series, the resistivity increases drastically with increasing delta. In polycrystals, in particular, there is mounting evidence that the oxygen deficiency and with it the resistivity is increased close to grain boundaries. Therefore, under a current load the electrical field near a grain boundary could be strong enough to induce a transition to a metallic state in a thin layer near the boundary. If, however, this sample part gets metallic, the electrical field is screened and the layer would return to its original state. As this looks like an electrical feedback mechanism, we expect that at least some manganites show electrical switching phenomena, and indeed these are observed. Numerical SPICE simulations and their comparison with the unusual experimental results, which were obtained with polycrystalline Nd0.7Sr0.3MnO3-delta and Pr0.7Ca0.3MnO3 ceramic and its Sr-substitution derivates, confirm both the existence of electrical field induced transitions and of an electrical feedback mechanism. (c) 2009 American Institute of Physics. [DOI: 10.1063/1.3087547]
Keywords: Magnetoresistance